Trait Emotional Intelligence, Siblings Relationship, & Interpersonal Difficulties in Young Adults - javaid, Laraib; Saba Walayat; Laiba Faz-ul-Rehman; Horain Fatima; Maida Noor, (Dialogue Social Science Review (DSSR), 2025)
Young adulthood (18–25 years) is a critical developmental stage marked by emotional, social, and psychological transitions. This study examines the relationship between trait emotional intelligence, sibling relationships (rivalry and conflict), and interpersonal difficulties among young adults. Using a quantitative correlational design, data was collected from 250 university students in Punjab, Pakistan, through stratified probability sampling with age ranges from 18-25 years (M=1.31; SD=.464). Participants completed the Adult Sibling Relationship Questionnaire (Stocker et al., 1997), Wong and Law Emotional Intelligence Scale (Wong & Law, 2002), and Interpersonal Difficulties Scale (Saleem et al., 2014), along with a demographic sheet. Pearson product-moment correlation was used to assess the results between variables. It indicated that there is a negative relationship between emotional intelligence and interpersonal difficulties (r = -0.186, p< .01), suggesting that higher emotional intelligence reduces social challenges. In contrast, a weak but significant positive correlation (r = .114, p< .05) between sibling relationships and interpersonal difficulties highlights the impact of sibling rivalry and conflict. However, no significant correlation was found between emotional intelligence and sibling relationships (r = .044, p=ns). Multiple regression analysis showed that sibling relationships and emotional intelligence together accounted for 5% of the variance in interpersonal difficulties (R² = .050, p< .006). These findings emphasize the role of emotional intelligence in reducing interpersonal difficulties and suggest that sibling interactions influence social relationships. Future research should explore additional social and environmental factors affecting interpersonal challenges. Keywords. Emotional intelligence, sibling relationships, interpersonal difficulties, young adulthood.